A comparative analysis of rural banks' efficiency between Bali and West Java provinces in Indonesia. (2nd October 2021) - Anwar, Mokhamad; Rahman Nidar, Sulaeman; Komara, Ratna; Layyinaturrobaniyah, Layyinaturrobaniyah
ABSTRACT: This study comparatively analyses rural banks' efficiency in Indonesia, especially in two provinces, West Java and Bali. West Java is known as the most populous province in Indonesia, , while Bali is the best province in rural bank performance through the assessment of Infobank Magazine in Indonesia, during the 2012–2016 Period. The study involves 212 banks in West Java and 134 banks in Bali over the period. Data envelopment analysis and Tobit regressions are employed to estimate the banks' technical efficiency and its determinants. The results show that the average efficiency of rural banks in Bali was higher than in West Java during the period. Inferential findings emphasize the importance of efficient resource use, sound loan-management, and adequate capital maintenance in bank operations. All these are required for rural banks to compete with other institutions including commercial banks and financial technology-based institutions in providing loans to micro and small businesses.